Protection of Crops and Animal Intrusion Detection System - J. Amutharaj, Dineshkumar M, Amrutha N S, Hithashree V, Meghana G (International Journal of Advanced Science and Technology, 2020)
IOT can be described as system of physical articles associated through Internet. This IOT based savvy cultivating is utilized to screen the harvest field with various sensors such as downpour sensor, mugginess sensor and dampness sensor. The dampness detector was utilized to examine the dampness quality, moistness detector works with checking the room temperature, downpour sensor which predominantly gives the message about unpredicted precipitation in the harvest field and they utilize programmed drying sheds and utilization of overabundance downpour water after different needs. Untamed life checking and investigation are in dynamic research fields since last numerous decades. This work mainly concentrates on creature identification from common scenes gained by camera and intimates the farmland owner and also stored the images in the camera trap database. This camera trap database is utilized to track the animals which enter into the farm land and damaging the crops. This paper proposes a creature recognition model which applies self learned Deep Convolution Neural Network (DCNN). This effective list of capabilities is used for calculation using names bolster vector machine and k-closest neighbor algorithms. The experimental results show that efficient discovery model using DCNN which give exactness of 91.4% from camera trap database.